Educação do campo : um estudo sobre cultura e currículo na Escola Municipal de Ensino Fundamental Crubixá - Alfredo Chaves - Espírito Santo - Klein, Sonia Francisco (2013)
The study, linked to Line Culture Research, Curriculum and Training of Educators, the Graduate Program in Education of the Federal University of Espírito Santo, and the Research Group Culture, Partnerships and Rural Education, investigates how knowledge and cultures peasant contribute to the formation of the curriculum of the Municipal School of Basic Education Crubixá the municipality of Alfredo Chaves - Holy Spirit. The study aims to know how to configure general knowledge and peasant cultures in the school curriculum. And specifically examines the curriculum practiced and its relationship with culture is not school. Discusses the knowledge and cultures of the community interface with the curriculum. The qualitative research, with contributions from the case study, favored the production of dialogical practices with research subjects, with survey data from various sources, which include document analysis, observation of the school environment and praxis teaching the teacher in the classroom, interviews with students, school staff and local community. Uses the theoretical framework of Eagleton (2011), Foerste (2004), Forquin (1993), Freire (2011), Geertz (1989), Sacristan (2000), Williams (2011) and others to build the foundations of reflection of Education field of culture, curriculum and collaborative interagency. The research shows that the contribution of knowledge and peasant cultures for pedagogical praxis school constitutes an ongoing process articulated in / teaching practice in interaction with the subjects in the school and community. Puts in question the existence of two fronts pedagogical work: the first, sets the bridge between everyday knowledge and peasant cultures in the curriculum and practiced second front, occurs sporadically in the context of lessons. It can be argued that this situation is linked to the continuing education of teachers, according to data analyzed in the research process. Given this reality, realizes the need for continuing education for teachers working in the school field with a view to increasing research and collaborative practices in social contexts where it is the Field Education as praxis of dialogue